TEACHER STRATEGIES IN DIRECTIVE SPEECH ACT ON THE GROWTH OF PANCASILA CHARACTER IN STUDENTS - Sari, Asri Wahyuni; Laila, Aruna; Putri, Febrina Riska; Armet, Armet; Yulisna, Risa (ppjbsip, 2022)
This study aims to find the form and function of teacher speech strategies in the learning process in the classroom in Indonesian. This research uses a qualitative descriptive approach with a pragmatic approach. The research data were obtained through observation and in-depth interviews. Data analysis is carried out by using qualitative techniques by reducing data, presenting data, and drawing conclusions from existing data. The results showed that the use of directive speech acts was of the type of ordering, asking, advising, warning, and solicitation. The strategy used is to speak frankly without further ado, positive politeness, negative polite preamble, and vague strategy. The functions used are the competitive function of 'competing', the friendly function of 'fun', and the collaborative function of 'cooperating' in the teacher's speech act in the teaching and learning process